Buku Pengayaan Pembelajaran Cerita Fabel Berbasis Literasi untuk Siswa Sekolah Dasar - Moh. Fakhri Nuha; Yuni Pratiwi; Nurchasanah Nurchasanah (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2019)
Abstract: This research was aimed to produce a book supporting fable-based literacy learning for elementary school students. This research model adopted from the model 4D development. As for this research generates. First, the product was developed with a base of basic literacy. Second, the theme of the story is developed with reference to the student text book. Third, a character story using animals endemic to Indonesia. Fourth, the storyline was developed by integrating values character education. Fifth, equipped with practice questions to guide students' understanding. Sixth, the use of language is adjusted to the criteria of elementary school students. Seventh, the design of the illustrations presented in full and interesting so that it can develop the visual intelligence of students. Based on the results of validation tests, practitioner tests, field tests, and corrective actions of the products developed it is feasible to be implemented.Abstrak: Penelitian ini bertujuan untuk menghasilkan buku pengayaan pembelajaran cerita fabel berbasis literasi baca-tulis untuk siswa sekolah dasar. Model penelitian ini mengadopsi dari model pengembangan 4D. Hasil penelitian sebagai berikut. Pertama, produk dikembangkan dengan basis literasi baca-tulis. Kedua, tema cerita dikembangkan dengan mengacu buku teks siswa. Ketiga, tokoh cerita menggunakan binatang endemik Indonesia. Keempat, alur cerita dikembangkan dengan mengintegrasikan nilai-nilai pendidikan karakter. Kelima, memuat latihan pertanyaan untuk menuntun pemahaman siswa. Keenam, penggunaan bahasa disesuaikan dengan kriteria siswa sekolah dasar. Ketujuh, desain ilustrasi disajikan secara penuh dan menarik sehingga dapat mengembangkan keecerdasan visual siswa. Berdasarkan hasil uji validasi, uji praktisi, uji lapangan, dan tindak perbaikan produk yang dikembangkan telah layak untuk diimplementasikan.